1978
DOI: 10.1042/bj1760159
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins in human erythrocytes during cell fusion induced by oleoylglycerol

Abstract: 1. The fusion of human erythrocytes into multicellular bodies that is induced by microdroplets of oleoylglycerol was investigated by optical and electron microscopy, and by gel electrophoresis of membrane proteins. 2. At the highest concentrations of oleoylglycerol and Ca(2+) used, at least 80% of the cells fused after 30min at 37 degrees C and only about 5% of the cells had completely lysed; the shapes of fused multicellular bodies were usually retained in ;ghosts' prepared by hypo-osmotic lysis. 3. The rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 36 publications
4
17
1
Order By: Relevance
“…Among the questions raised by such multiplicity of proteinases, a major one is that of defining specific roles for each proteinase in terms of protein substrates, accessibility of soluble proteins to their site of degradation, selective mechanisms of regulation etc. Thus, for instance, Quirk et al (1978) have reported that band 3, the major protein of erythrocyte membranes, may be a substrate for a specific proteinase activity in erythrocytes induced to fuse by treatment with oleoylglycerol. A possibly related system has been described by King & Morrison (1977), who have attributed some significant changes in membrane proteins to a Ca2+-activated proteinase.…”
Section: Discussionmentioning
confidence: 99%
“…Among the questions raised by such multiplicity of proteinases, a major one is that of defining specific roles for each proteinase in terms of protein substrates, accessibility of soluble proteins to their site of degradation, selective mechanisms of regulation etc. Thus, for instance, Quirk et al (1978) have reported that band 3, the major protein of erythrocyte membranes, may be a substrate for a specific proteinase activity in erythrocytes induced to fuse by treatment with oleoylglycerol. A possibly related system has been described by King & Morrison (1977), who have attributed some significant changes in membrane proteins to a Ca2+-activated proteinase.…”
Section: Discussionmentioning
confidence: 99%
“…In ghosts of human erythrocytes, the immobility of the intramembranous particles is well known and aggregation, similar to that of fig3c, is seen only after partial removal of spectrin [21]. When intact human erythrocytes were fused by oleoylglycerol, a loss of micro-aggregation in the intramembranous particles of the treated cells implied that the particles were at least partially free to move [22]. Figure 3d shows that the proteinase inhibitor PMSF, which inhibited cell fusion induced by subtilisin Carlsberg (fig2c), also inhibited the loss of intra-membranous particles and their thermally-induced, lateral movement in the membranes of enzyme-treated cells.…”
Section: Cell Fusion Induced By Exogenous Proteinasesmentioning
confidence: 99%
“…However, it is much more likely that Ca2+ entry is a consequence, not a cause, of an altered membrane, since chemical fusogens increase membrane permeability in general, as demonstrated by Knutton & Pasternak (1979) and by Blow et al (1979) themselves. Moreover EDTA does not abolish cell-cell fusion of human erythrocytes (Quirk et al, 1978). What is probably true is that the stability of giant cells (polykaryons) requires the presence of some Ca , Table 4.…”
Section: Ca2+ Effect On Virus-cellfusionmentioning
confidence: 99%